Application of Shift and Share Technique for Forecasting Regional and Sectoral Growth in India for the Sixth Plan Period - Planning Commission (Planning Commission, 1982)
This paper examines the application of the Shift and Share technique to forecast regional and sectoral growth patterns in India during the Sixth Plan period (1980–1985). By decomposing growth into national, industry mix, and regional competitive effects, the study provides insights into differential state performance and sectoral specialization. Using historical state domestic product data, the analysis identifies significant regional disparities, with states such as Maharashtra and Haryana exhibiting strong industrial and service-sector growth, while others lag behind. The projections highlight a structural shift from agriculture toward manufacturing and services, underscoring the need for balanced regional planning. Despite its limitations, the Shift and Share method is shown to be a practical and informative tool for policy formulation, resource allocation, and achieving more equitable regional economic development in India.
Government of India Planning Commission (UNDP Transport Policy Planning Project)
Government of India Planning Commission (UNDP Transport Policy Planning Project)
Keywords: Shift and Share Technique; Regional Economic Growth; Sectoral Growth Forecasting; Sixth Five Year Plan; State Domestic Product; Industry Mix Effect; Regional Competitiveness; Balanced Regional Development; Sectoral Specialization; Economic Planning In India